University in a Small City Environment: Campus Vibes - Georgiy V. Korshunov; Inna O. Vedernikova; Sergey Yu. Dubikovsky (Moscow Polytechnic University, 2019)
The article explores the phenomenon of strong nexus between the development strategies of small cities, claiming for the status of supporting regional cities, and universities located there. The university community and urban public are inclined to the positioning of such cities as "university cities". The authors dwell on the role of campuses in the implementation of the "third mission" by universities. Particular consideration is given to the specific component of the third mission and, accordingly, the campus infrastructure for the development of local communities, urban and regional environments. A model of the regional environment monitoring system is described, which is based on the system of sociological surveys including five subsystems (questionnaire of employers, questionnaire of schoolchildren aimed at vocational guidance, questionnaire of parents, questionnaire of communities, and internal monitoring). The article also focuses on the forms of using campus facilities for the implementation of various events and social projects involving the local community and aimed at the development of the urban and regional environment in the following areas: consolidation, education and community assistance, social mobilization and public branding.